TIME VARIATION EFFECT ON UNCONFINED COMPRESSIVE STRENGTH VALUE ON CLAY AND SILT STABILIZED USING CEMENT ON SOAKING CONDITION - Syananta, Dindha Amalia; Adha, Idharmahadi; Setyanto, Seytanto (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2016)
Soil in Indonesia are mostly clay and silt, which tend to be unstable, such as the soill support,compressive strength of soil and land subsidence. Unconfined Compression Test is a method thatdone in the laboratory to measure compression until the soil separates from its grains and tomeasure the soil stretch from that press. In this research to improve the quality of the soil usedmaterials like cement mixer with a variety of curing 7 days, 14 days and 28 days in order todetermine the optimum strength in clay and silt.From the effect of variations in curing time on compressive strength test values obtainedincrease in the compressive strength at the highest cement mix with a variety of curing time of 14days at 0.5927 kg /cm 2 for clay. On the silt soil increase in the compressive strength with thehighest free 14-day curing time variation of 0.5819 kg / cm2. Under optimal conditions theinfluence of a mixture of cement on clay and silt soil occurred in 9% of cement mix with a curingtime of 14 days. From the results obtained show consistent with an increase in cement content,an increase in the value of qu. With increasing curing time then the compressive strength alsoincreased.Keywords: compressive strength, cement, curing, clay, silt